Pengaruh Atribut Produk, Komitmen Agama, Kualitas Pelayanan, dan Kepercayaan Terhadap Loyalitas Nasabah dengan Kepuasan Sebagai Variabel Intervening - Elsandra, Yesi; Efriyuzal, Efriyuzal (Jurnal Ekonomi, 2013)
Goal of this research are to recognize and analyze the influece of product attribute, commitment religion, service quality and believe to customer satisfaction; the influence of product attribute, religion, service quality and beliave to customer loyality; and the influence of product attribute, religion, service quality and believe to loyality through customer satisfaction. The object of this research are Bank Syariah Mandiri Muaro Bungo Barnch customers with 91 number of samples using simple ramdom sampling methode. The result shows that in every point of research goals, product attribute, religion, service quality and believe have significant influence.